Ultra-High-Performance Concrete Crack Propagation Based on Fiber Random Distribution Model - Yu, Ziruo; Liang, Weizhi; An, Mingzhe; Wang, Yue (Frontiers in Materials, 2022)
The tensile strength, crack behavior, and strain-hardening properties of ultra-high-performance concrete (UHPC) are mainly affected by the steel fibers distributed in the matrix. In this study, a mesoscopic model of UHPC was established using a numerical simulation method to study the effects of steel fibers on the crack propagation and tensile properties of UHPC. First, the exponential cohesive model was used to simulate the pull-out of a fiber embedded in a UHPC matrix. Then, the distribution and variation of the interfacial shear stress during the fiber pull-out process were obtained, and the UHPC fiber-pull-out load–displacement curve was obtained. Using the Monte Carlo method, a meso-scale finite element model of UHPC was established by modeling randomly distributed steel fibers in the UHPC matrix. After verification, the model was used to study the effects of fiber characteristics, interface strength, and matrix strength on the crack propagation path and tensile properties of UHPC. The results showed that the exponential cohesive constitutive model with a softening coefficient of –1 can effectively characterize the mechanical behavior of the interface between the steel fibers and matrix in UHPC. Affected by the random distribution of fibers, the main propagation mode of cracks in UHPC was that the cracks bypassed the fiber-dense area and extended to the fiber-sparse area, and the crack propagation path was mainly affected by the fiber distribution. The distribution of fibers significantly affected the tensile strength and peak strain of UHPC. When the fiber inclination angle was in the range of 15°–30°, the comprehensive tensile properties of UHPC were the best. With increasing fiber volume fraction and fiber length, UHPC gradually began to exhibit multi-cracking and strain hardening (when the fiber volume fraction was more than 2.5% or fiber length was more than 15.5 mm). The interface strength and matrix strength had little effect on the crack propagation path, but had significant effects on the tensile strength and toughness of the UHPC. The higher the strength of the UHPC matrix, the more fully the anti-cracking effect of the steel fiber that can be achieved.